Vitamin B12 Protects against Genotoxicity Induced by Cisplatin - Al-Bataineh, Wejdan M.; Alzoubi, Karem H.; Khabour, Omar F.; Mahasneh, Amjad; Al Momany, Enaam M. (Current Cancer Drug Targets, 2024)
Background: Cisplatin is an effective synthetic chemotherapeutic drug used for cancer treatment. Vitamin B12 has been shown to possess anti-genotoxic activity. This study aimed to investigate the effect of vitamin B12 on chromosomal damage induced by cisplatin. Methods: The level of sister chromatid exchanges (SCEs) and chromosomal aberrations (CAs) were measured in cultured human blood lymphocytes treated with cisplatin and/or vitamin B12. Results: The results showed a significantly elevated frequency of CAs and SCEs of cisplatin-treated cultures compared to the control (P < 0.05). The CAs and SCEs induced by cisplatin were significantly lowered by pretreatment of cell cultures with vitamin B12. In addition, cisplatin caused a slight reduction in the mitotic index (MI), while vitamin B12 did not modulate the effect of cisplatin on MI. Conclusion: Vitamin B12 can protect human lymphocytes against genotoxicity associated with cisplatin.
Keywords: cisplatin